Phenotype and genetic variation analysis of primary congenital lymphedema caused by FLT4 gene mutations in a fetus - Zhai, Shanshan; Yuan, Limin; Li, Jing; Liu, Ling; Hu, Lulu; Ban, Yanjie; Yang, Xuewen; Yang, Jie; Ouyang, Xuezhe; Huang, Nana; Tian, Yuan; Wang, Ting; et al. (Frontiers in Genetics, 2025)
IntroductionThe purpose of this retrospective study was to investigate the imaging phenotype and genetic variation of three fetuses with FLT4 gene mutations in three families.MethodUltrasound images of the three affected fetuses were collected; fetal specimens were obtained by amniocentesis, and peripheral blood samples were collected from both parents for whole-exome sequencing (WES) and copy number variation sequencing (CNV-seq).ResultThe primary prenatal imaging phenotype of fetuses from three families showed bilateral lower limb and foot dorsum lymphedema. Genetic testing identified a paternal c.3122G>A (p.R1041Q) heterozygous variant of the FLT4 gene (NM_182925.5) in the family 1 fetus, a paternal c.3284G>A (p.S1095N) heterozygous variant of the FLT4 gene (NM_182925.5) in the family 2 fetus, and a maternal c.2560G>A (p.G854S) heterozygous variant of the FLT4 gene (NM_182925.5) in the family 3 fetus. Postpartum follow-up: the fetus in family 1 mainly presented with bilateral foot dorsum lymphedema at birth, which improved significantly after surgical treatment at 1 month of age; the fetus in family 2 had mild lymphedema in both feet at birth, which significantly subsided at 18 months of age; the pregnancy was terminated in family 3.DiscussionBilateral lower limb lymphedema is a typical clinical manifestation during the fetal stage. Some cases follow a benign course of natural regression, whereas some cases achieve a good prognosis via surgical intervention. The FLT4 c.3284G>A variant identified in this study has not been previously reported, which broadens the mutation spectrum of this gene. In this study, we provide valuable insights for prenatal diagnosis, genetic counseling, and prognosis evaluation of the disease.